3D printed polymeric drug-eluting implants for personalized therapy - Liaskoni, Athina (2022)
Conventional oral drug delivery systems, such as tablets, capsules and solutions, are widely used today and is the most commonly selected mode of administration for patient treatment. These systems can, however, demonstrate limitations, including the need for their frequent administration so that drug therapeutic levels can effectively be achieved and maintained. This can lead to reduced patient compliance, especially in populations having multiple and multiplex conditions, that need to be treated with several active ingredients contained in different formulations - in the UK, patients over 65 years of age take on average 5 to 8 different medications per week. For certain clinical needs, this requirement for frequent administration can be avoided by the use of long-acting implants. In addition, personalised medicine is a new approach that can reduce medication burden, since the fabrication of bespoke dosage forms is based on an individual’s health status, needs, genetic and physical factors.